2011
DOI: 10.4103/0019-5049.89898
|View full text |Cite
|
Sign up to set email alerts
|

A critical incident report: Propofol triggered anaphylaxis

Abstract: Although propofol is one of the most commonly used drugs for induction of anaesthesia, it is not devoid of anaphylactic potential. Early detection of any suspected anaphylactic reaction during anaesthesia, prompt management, identification of the offending agent and prevention of exposure to the offending agent in the future is the responsibility of the anaesthesiologist. This is a case report of anaphylaxis to propofol at the induction of anaesthesia in a previously non-allergic 56 year-old man, planned to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…The authors concluded that it was due to the isopropyl or phenyl group, rather than the intralipid emulsion, in these cases. This is also supported by other reports of patients without food allergies reacting to propofol . Recently there have been cases of allergy to ethylenediamine tetra‐acetic acid (EDTA), another excipient in propofol .…”
Section: Discussionsupporting
confidence: 72%
“…The authors concluded that it was due to the isopropyl or phenyl group, rather than the intralipid emulsion, in these cases. This is also supported by other reports of patients without food allergies reacting to propofol . Recently there have been cases of allergy to ethylenediamine tetra‐acetic acid (EDTA), another excipient in propofol .…”
Section: Discussionsupporting
confidence: 72%
“…This emulsion was specifically designed to avoid allergic reactions in egg‐ or soy‐allergic patients, considering that soybean oil is highly refined with almost nonallergenic content after the refining process and egg lecithin comes from egg yolk, being the most allergenic proteins contained in egg white . Over the last 25 years, several cases of anaphylaxis or allergic adverse events after propofol administration have been reported , presumably related in most cases to cross‐reactivity with food allergies.…”
mentioning
confidence: 99%
“…In the Previously reported studies, anaphylaxis -like reactions varied from mild to severe category, the extreme case being a direct cardiac arrest. Respiratory symptoms were absent in some anaphylaxis events [1]. Most of the patients received standard treatment for anaphylaxis.…”
Section: Resultsmentioning
confidence: 98%
“…Most of the patients received standard treatment for anaphylaxis. Some patients needed continuous infusion of adrenaline as a life-saving measure [1]. When many drugs are involved, it is difficult to identify the causative agent for anaphylaxis.…”
Section: Resultsmentioning
confidence: 99%